Promoting Multiculturalism in Southeast Asia: Is There a Lesson We Can Learn from Canada’s Experience? - Afrianty, Dina (Studia Islamika, 2011)
This conference was organized with the idea to discuss some crucial issues that challenge global society, in particular, state-government in facing an increasingly globalised world. Society becomes more diverse and complex as a result of infiltration of other cultures and people movements. This situation poses serious challenges for state-government and civil society to ensure that complex social cohesion will not lead to tension and conflict both among members of the society and between the state and the society.DOI: 10.15408/sdi.v18i2.438